Energy transfer in Anabaena variabilis filaments adapted to nitrogen-depleted and nitrogen-enriched conditions studied by time-resolved fluorescence - Onishi, Aya; Aikawa, Shimpei; Kondo, Akihiko; Akimoto, Seiji (Photosynthesis research, 2017)
Nitrogen is among the most important nutritious elements for photosynthetic organisms such as plants, algae, and cyanobacteria. Therefore, nitrogen depletion severely compromises the growth, development, and photosynthesis of these organisms. To preserve their integrity under nitrogen-depleted conditions, filamentous nitrogen-fixing cyanobacteria reduce atmospheric nitrogen to ammonia, and self-adapt by regulating their light-harvesting and excitation energy-transfer processes. To investigate the changes in the primary processes of photosynthesis, we measured the steady-state absorption and fluorescence spectra and time-resolved fluorescence spectra (TRFS) of whole filaments of the nitrogen-fixing cyanobacterium Anabaena variabilis at 77 K. The filaments were grown in standard and nitrogen-free media for 6 months. The TRFS were measured with a picosecond time-correlated single photon counting system. Despite the phycobilisome degradation, the energy-transfer paths within phycobilisome and from phycobilisome to both photosystems were maintained. However, the energy transfer from photosystem II to photosystem I was suppressed and a specific red chlorophyll band appeared under the nitrogen-depleted condition.